The Effect of Lipid Profile and Blood Glucose on Hypertension At Pasar Minggu District Health Center - Ery Kustini; Munaya Fauziah; Suherman Suherman; Dewi Purnamawati; Abul A’la Al Maududi (Yayasan Pendidikan Penelitian Pengabdian Algero, 2025)
Hypertension remains a leading metabolic risk factor contributing to morbidity and mortality, particularly in Indonesia’s urban populations. This study examined the effect of lipid profile and blood glucose on hypertension incidence among non-communicable disease (NCD) clinic patients at Pasar Minggu District Health Center, South Jakarta. A cross-sectional design was applied, utilizing secondary data from electronic medical records (e-puskesmas) in 2023. The study involved 1,168 patients. Results showed that 88.7% had hypertension, with 65.3% exhibiting high LDL levels, while most had non-risk levels of total cholesterol (57%), HDL (52.7%), triglycerides (67.1%), creatinine (90.5%), and HbA1c (74.6%). Multivariate analysis revealed significant associations between total cholesterol (OR=0.619; 95% CI=0.393–0.974) and HbA1c (OR=0.180; 95% CI=0.128–0.252) with hypertension incidence, after controlling for LDL. Elevated total cholesterol and HbA1c were linked to a reduced hypertension risk in this population. The findings suggest that integrating lipid and glucose control into hypertension prevention strategies, alongside multisectoral collaboration, may enhance early detection and management of NCDs in primary care settings.